166 EXPRESSION AND FUNCTION OF DUAL OXIDASE IN FETAL LUNG EPITHELIAL CELLS. (1st January 2006) - Fischer, H.; Illek, B.; Kolla, V.; Gonzales, L. W.; Ballard, P. L.
Abstract : Sterility of lung alveoli is normally maintained by an innate host defense system; however, infants born prematurely have developmental deficiencies in anti-microbial defense and are highly vulnerable to infection. Production of reactive oxygen species (ROS) by professional phagocytic cells contributes to bacterial killing, and ROS are also bacteriocidal in vitro. Dual oxidase 1 (Duox1), a homolog of phagocytic NADPH oxidase, is expressed in several epithelial tissues and catalyzes formation of superoxide (extracellular) and protons (intracellular). The objective of this study was to determine the rate of proton and ROS generation as well as Duox1 expression during differentiation of alveolar type II cells. Epithelial cells were isolated from human fetal lung (13-20 wk) and treated with dexamethasone + cAMP to induce type II cell differentiation. Duox1 expression was assessed by DNA microarray, Western and immunostaining. Production of protons and ROS was determined with fluorescent probes, pH stat titration in Ussing chambers, patch-clamp with whole cell proton conductance, and hydrogen peroxide assay. Exposure of cultured cells to hormones increased Duox1 mRNA by 3.8-fold ( n = 5) and protein ( n = 3) by 9-fold after 72 h. Immunostaining of lung explants revealed low expression of Duox1 in control tissue, whereas hormone-treated tissue strongly expressed Duox1 at the apical surface of epithelial cells. The rate of both intracellular production and release of protons was 6-fold higher in hormone-treated cells. Addition of amiloride to the serosal surface (inhibiting Na + /H + exchanger) increased acid secretion by 30%, whereas ZnCl2 added to the mucosal surface inhibited secretion by 80%, indicating that cells secrete protons via an apical proton conductance. Biophysical properties of proton conductance were unchanged by hormone exposure, suggesting that increased acid secretion occurs secondary to elevated intracellular production of protons. Hormone-treated cells produced hydrogen peroxide (≈200 pmol/cm 2 /h), which was decreased 60% in the presence of Duox1-specific siRNA. We conclude that differentiation of type II cells is associated with up-regulation of Duox1 and increased extracellular production of ROS, which may contribute to alveolar host defense against microorganisms. Immaturity of alveolar defense mechanisms, including alveolar content of ROS, contributes to the susceptibility of premature infants to pulmonary infections.